Supplementation of Molasses-Based Liquid Feed for Cattle Fed on Limpograss Hay - Daciele Abreu; José C. B. Dubeux; Luana Dantas Queiroz; David Jaramillo; Erick Rodrigo Da Silva Santos; Flávia van Cleef; Carlos Vela-Garcia; Nicolas DiLorenzo; Martin Ruiz-Moreno (Animals, 2022)
Two experiments were performed to evaluate the effects of (1) different levels of liquid supplementation (LS) based on molasses enriched with 32% (as fed; 45% on DM basis) crude protein (CP) on intake of Hemarthria altissima hay (LH), digestibility, and rumen fermentation, and (2) different levels of LS based on molasses enriched with 32% CP in the in vitro gas production in LH diets. In Exp. 1, twelve heifers and 12 adult male castrated and cannulated cattle were used. Treatments were allocated in a randomized block design, in four treatments: (CTL) access ad libitum to the LH; (SUP2) ad libitum access to LH and supplementation with 0.9 kg d−1; (SUP4) ad libitum access to LH and supplementation with 1.8 kg d−1 and; (SUP6) ad libitum access to LH with 2.7 kg d−1. In Exp. 2, treatments were carried out in a randomized block design with four different proportions of LH diet: (CTL) 100 LH, (SUP2) 85 LH and 15 LS, (SUP4) 70 LH and 30 LS, (SUP6) 55 LH and 45% LS. In Exp. 1, liquid molasses-based supplementation did not affect LH intake (p > 0.05). Molasses intake improved as the supply increased, not reducing the intake of LH. In Exp. 2, the addition of LS to the LH caused a change in the VFA profile, with an increase in propionate production in vitro.